Theistic Democracy Studies Hadith Analysis Deliberations in Contemporary Islamic Political Ethics - Mahasin Haikal Amanullah; Muhammad Adip Fanani (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2024)
Islam is a religion that exists as a religion today, where many universal questions are discussed, one of the main topics of today's big questions is democracy in politics. Although Islam talks about democracy, ironically, Islam itself does not specifically mention the ideal form of a political system. In this context, the discussion about the ideal political formula becomes clearly important among Muslims in modern times, especially against the backdrop of Western civilization which can be said to have destroyed Muslims with its culture. In the midst of this chaotic situation, contemporary Muslim intellectuals present as Muslim thinkers who seek to present the "ideal" concept of modern Islamic politics. In this study, the author tries to emphasize that the substantive principles of Islam must be applied in the country's political system, in this case theistic democracy exists as a legacy from the problematic modern state. Democracy, or deliberation in Islamic nomenclature, is one of the ethical values ​​of constitutional politics in current political life.